Dirty nevus - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 17-year-old girl was observed for evaluation of nevi and in particular of a nevus of the neck. Her family history was negative for melanoma, the personal history did not indicate severe illnesses, nor in particular primary or secondary immune deficiency; she did not report congenital nevi. On physical examination, there were fifteen acquired 1-4 mm in size melanocytic nevi of on her head, trunk and limbs. On the left cervical region there was a raised papillomatous nevus of about 5 mm completely covered with scales affecting also the surrounding skin (Fig. 1). In a supplement of history the girl reported that when washing she stopped at due distance from the mole for fear that it could degenerate. The final diagnosis was dirty nevus and we reviewed the girl after she had cleaned with water and soap the nevus and the surrounding area